Didactic Suitability of the Instructional Process on Quadrilaterals in a Book and as Implemented by Elementary School Teachers - Castillo Céspedes, María José (2025)
[Objective] The objective of the study was to analyze and compare the level of didactic suitability of instructional processes related to the study of quadrilaterals, starting with the analysis of a primary education book that addresses the topic, followed by the analysis of two lessons actually implemented by teachers who used the book as a resource, examining their actions to evaluate whether or not they improved the process outlined in the book. [Methodology] After the level of didactic suitability of the book was determined, a case study was carried out with two primary school teachers (one novice and one expert) who used the same book in the fourth year of elementary school to teach the lessons on quadrilaterals. For the analysis, the didactic suitability indicators of a general analysis guide of instructional processes were adapted to the topic of quadrilaterals, to the educational level (elementary) and to the Costa Rican curriculum. [Results] The level of suitability of the instructional process outlined in the book was medium (on a high, medium or low scale), containing some weaknesses and mathematical errors. The instructional processes implemented by both teachers were less appropriate than the ones described in the book, although there were no significant differences. There were few actions implemented by the teachers that resulted in an improvement of the instructional process used in the book. [Conclusions] The levels of adequacy of the processes implemented by the teachers were below the level of the process outlined in the book, presenting errors and weaknesses specific to the book and amplifying them. It is necessary to provide opportunities for teachers to improve their ability to use the book critically as well as their didactic-mathematical knowledge. The indicators adapted can be used to support teachers in these tasks.